Differential Levels of Nutrients and Heavy Metals in Tilapia Collected from Drains in Egypt - Burch, Emily (AUC Knowledge Fountain, 2023)
Tilapia is one of the most widely cultivated and consumed fish globally. In terms of human health, tilapia is an excellent source of protein, polyunsaturated fatty acids, and micronutrients. Tilapia and other aquatic species have become increasingly susceptible to contamination, as anthropogenic activities have been increasing around the world. Anthropogenetic activities often introduce high levels of contaminants, including heavy metals, into the marine environment. These contaminants often do not biodegrade, and they are absorbed by aquatic species. Contaminants can bioaccumulate and proceed in biomagnification up the fish food chain putting consumers at an increased risk of exposure. Heavy metals can be toxic to humans even when consumed in small quantities. Tilapia samples were collected from drains in various locations in Egypt including Cairo, Alexandria, Ismailia/Port-Said, Aswan, Fayoum, and Kafr-El Sheikh. Tilapia samples collected from this study were evaluated using ICP-MS to determine the heavy metal concentration, the nutrient profile was also evaluated and included crude fiber, protein, and lipid percentages. Estimated weekly Intakes related to Mercury and Cadmium were above the Provisional Tolerable Weekly Intake set by the Joint FAO/WHO Expert Committee on Food Additives and Tolerable Weekly Intake set by European Food Safety Authority. Mercury was found to have a Target Hazard Quotient (Non-carcinogenic risk) above the suggested reference level. The concentrations of other heavy metals including Chromium, Nickle, and Lead were found to potentially increase an individual’s risk of developing cancer. Significant correlations (P<0.05) were observed in this study between heavy metals and macronutrient composition. The findings of this study indicate that certain individuals in the Egyptian population may be at a potentially increased risk of adverse health effects related to heavy metal toxicity from tilapia consumption. Children may be at the highest risk of developing adverse side effects related to heavy metals. Mercury was observed to be the only heavy metal to show an increased risk of noncarcinogenic side effects. The carcinogenic risk was suggested with Chromium, Nickle, and Lead concentrations in tilapia samples collected in this study. Further studies need to be conducted on the relationship between heavy metal contamination and nutrient composition. The results of this study suggested that fat content may be directly correlated with increased heavy metal concentrations of Chromium, Copper, and Zinc.